SANGGRALOKA PEGUNUNGAN KAWASAN PANTAI GEDAMBAAN KOTABARU KALIMANTAN SELATAN - Irhammi, Muhammad; Nurfansyah, Nurfansyah (UNIVERSITAS LAMBUNG MANGKURAT, 2020)
Resorts in general, are tourism objects that utilize the natural potential that is sensitive to the environment, which is an architectural product that is environmentally friendly and sustainable with the surrounding environment. One of the tourist areas in South Kalimantan that has exotic natural potential is Kotabaru Regency. The beach and the mountains are the tourism places of Kotabaru Regency which are the main icons. The resort is one of the developing tourism in Indonesia, especially in areas with beautiful mountains and beaches. From this phenomenon, an idea emerged to present a resort that could exploit the natural potential in the mountainous area of ​​Kotabaru Regency to create a resort that can meet the needs of tourists, Contextual concept is used.